Chinese medicine Phragmites communis (Lu Gen) for acute respiratory tract infections: a systematic review and meta-analysis of randomized controlled trials - Fang, Min; Kong, Ling-Yao; Ji, Guang-He; Pu, Feng-Lan; Su, You-Zhu; Li, Yu-Fei; Moore, Michael; Willcox, Merlin; Trill, Jeanne; Hu, Xiao-Yang; Liu, Jian-Ping (Frontiers in Pharmacology, 2024)
Background: Acute respiratory tract infections (ARTIs) are the most common cause of morbidity and mortality worldwide, with most people experiencing at least one episode per year.Current treatment options are mainly symptomatic therapy.Antivirals, antibiotics, and glucocorticoids are of limited benefit for most infections.Traditional Chinese medicine has shown potential benefits in the treatment of ARTIs.Objective:To determine the efficacy, effectiveness, and safety of Phragmites communis Trin. (P. communis, a synonym of Phragmites australis (Cav.) Trin. ex Steud) as monotherapy or as part of a herb mixture for ARTIs.Method: Eight databases and two clinical trial registries were searched from inception to February 8, 2023, for randomized controlled trials (RCTs) evaluating any preparation involving P. communis without language restrictions. The Risk of Bias Tool 2.0 was used to assess the risk of bias of included trials. Revman 5.3 software was used for data analyses with effects estimated as risk ratios (RR) or mean differences (MD) or standardized mean differences (SMD) with 95% confidence intervals (CI). The online GRADEpro tool was used to assess the certainty of the evidence, if available.Results: Forty-two RCTs involving 6879 patients with ARTIs were included, with all trials investigated P. communis as part of a herbal mixture. Of the included trials, majority (38/42) were considered high risk.Compared to placebo, P. communis preparations improved the cure rate [RR=1.60, 95% CI (1.13, 2.26)] and fever clearance time [MD=-2.73h, 95% CI (-4.85, -0.61)].Compared to usual care alone, P. communis preparations also significantly improved the cure rate [RR=1.57, 95% CI (1.36, 1.81)] and fever clearance time [SMD=-1.24, 95% CI (-2.37, -0.11)]. P. communis preparations plus usual care compared to usual care alone increased the cure rate [RR=1.55, 95% CI (1.35, 1.78)], shortened fever clearance time [MD= ], improved FEV1 [n=6, MD=0.19L, 95%CI (0.13, 0.26)] . Conclusion: Low or very low certainty evidence suggests that P. communis preparations may improve the cure rate of ARTIs, shorten fever clearance time in febrile patients, and improve pulmonary function of patients with acute exacerbation of chronic obstructive pulmonary disease or chronic bronchitis.However, these findings are inconclusive and need to be confirmed in rigorously designed trials.